Escola e gênero : representações de gênero na escola - Bezerra, Josenildo Soares (2006)
The study Escola e Gênero: representações de gênero na escola show us the social man made, starting of an analysis in the having fun time in the children´s life and how it´s an important aspect of the building childish universe simbolic. My analysis started in a children´s daily at school and how they noticed the play value od dominant society. Our propouse is think about the linking between ideology, representations and gender like the children´s knowledge in the school activities. The toy, an instrument which is noticed and exist in the funny activities, is full of cultural concepts of male and female parts. Your color, lines, functions and the way you manipulate is driven of gender cathegories. In the scool, the ideological concepts have it´s important way which is to domesticate the feelings, the desires; categorize and normalize them without be known by the educational employers. In the children´s education, the funny time is noticed by others ways and turned as important as others subjects. By the way it´s not noticed by the school, like another thing which isn´t a funny moment. And it´s exactly here in the school funny time, the school did your cultural power of separete the gender and your extencions, feed by the society, generaly, in favor of the man whose woman is your subordinate. This ways of analysis help the society and the school universe about the funny time e how they are important in the Man made life. And how the toys bring the concepts and addicted thinking, ideological which put the power in the stages, without equal, addicted feelings around the gender concepts. I read and used the theories of Kishimoto, Berger & luckmann, Brougère, Sousa Filho, Bourdieu, Badinter, Geertz, Grossi, Louro, Foucault, among others